The EMF: topics for discussion - PADOA-SCHIOPPA, T. (PSL Quarterly Review, 2013)
This paper was presented at the Second International Seminar on European Economic and Monetary Union, held in Geneva in December of 1979. The work deals with the European Monetary Fund and the challenges it faces going forward. The author’s main concern is not so much to offer solutions as to provide the proper framework for finding them. Three main subjects are identified as constituting the pillars of the next stage of the European Monetary System: credit mechanisms, exchange rate arrangements, and the ECU. Each of these three pillars has to be built on solid foundations and in such a way as to allow progress from a “looser” to a “tighter” system. JEL: F33, F36